2022
DOI: 10.1002/hbm.25819
|View full text |Cite
|
Sign up to set email alerts
|

The differential association between local neurotransmitter levels and whole‐brain resting‐state functional connectivity in two distinct cingulate cortex subregions

Abstract: Reproducible resting-state functional connectivity (rsFC) patterns and their alterations play an increasing role in neuropsychiatric research. Studies that limit the analysis of metabolites and rsFC strengths to a predefined canonical network suggest that the rsFC strength positively correlates with the local glutamate (Glu) levels and negatively correlates with the gamma-aminobutyric acid (GABA) levels. The contribution of regional neurotransmitter activity to rsFC strengths from a given seed to the whole-bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 88 publications
(138 reference statements)
0
5
0
Order By: Relevance
“…The pgACC is involved in internal mental processes and processing affective information [45,46]. Glutamate concentrations are higher in rostral than caudal ACC regions [47] and differentially relate with whole brain resting state functional connectivity [48]. Early changes in pgACC connectivity predict antipsychotic response in FEP [30] and pgACC glutamate correlates with ACC control over sensory regions in antipsychotic-responsive but not treatment resistant schizophrenia [49].…”
Section: Discussionmentioning
confidence: 99%
“…The pgACC is involved in internal mental processes and processing affective information [45,46]. Glutamate concentrations are higher in rostral than caudal ACC regions [47] and differentially relate with whole brain resting state functional connectivity [48]. Early changes in pgACC connectivity predict antipsychotic response in FEP [30] and pgACC glutamate correlates with ACC control over sensory regions in antipsychotic-responsive but not treatment resistant schizophrenia [49].…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this this version posted November 22, 2022. ; https://doi.org/10.1101/2022.11.21.22282584 doi: medRxiv preprint and FC, suggesting their role in synchronizing brain activity across specific regions [22][23][24][25][26].…”
Section: (Which Was Not Certified By Peer Review) Preprintmentioning
confidence: 99%
“…In contrast to the growing knowledge of their functional properties, the neurochemical regulation of large-scale brain networks remains largely unknown. Studies applying combined magnetic resonance spectroscopy (MRS) and fMRI reported significant associations between the spectral signals of main inhibitory and excitatory neurotransmitters, gamma-aminobutyric acid (GABA) and glutamate (Glu), and FC, suggesting their role in synchronizing brain activity across specific regions [22-26]. Importantly, this was demonstrated for both regional and inter-regional (task-dependent) FC, but the direction of the association was variable depending on the brain region considered and on task-demand [26-28].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations